DADCQ Protocol and Attacks in VANET - A Literature Review - Choudhari, Dharmaveer P; Dorle, Sanjay S (International Journal of Computer Sciences and Engineering, 2019)
VANET provides the information in the dynamically changing environment in the rapidly changing topological environment so as to provide the seamless flow of data between the vehicles in the in ad-hoc environment. Basically VANET is the subset of MANET. For effective routing from the source vehicle to destination vehicle in the dynamic environment the broadcast protocol must withstand this dynamically changing topology of the network. The mobility of network in urban scenarios is highly variable so the protocol must be able to adapt changes as per the topology of VANET. Also the delay in network communication can cause loss of data packets which may be very dangerous from the driver’s point of view in VANET. The loss of data packets may occur due to large amount involved in the communication or another reason may the different types of attacks such as DDoS attack or eavesdropping attacks which will reduce the efficiency and security of the network to a great extent and harm the communication model. This paper focuses on the detection of the attacks such DDoS and Eavesdropping attacks and its effect to the protocol parameter such routing efficiency and mean delay. After detection of these attacks a novel solution is adopted from improving routing efficiency and mean delay of the protocol so as to make network reliable and more secure.